Addressing obesity in the first 1000 days in high risk infants: Systematic review. Issue 3 (29th March 2021) - Rossiter, Chris; Cheng, Heilok; Appleton, Jessica; Campbell, Karen J.; Denney‐Wilson, Elizabeth
Abstract: Early intervention is critical for addressing the challenge of childhood obesity. Yet many preventive interventions do not target infants most at risk of future overweight or obesity. This systematic review examines interventions delivered before 2 years that aim to ameliorate excess weight gain among infants at high risk of overweight or obesity, due to sociodemographic characteristics, parental weight or health status, infant feeding or health behaviours. We searched six databases for interventions: (a) delivered before age two, (b) specifically aimed at infants at high risk of childhood obesity and (c) that reported outcomes by weight status beyond 28 days. The search identified over 27, 000 titles, and 49 papers from 38 studies met inclusion criteria: 10 antenatal interventions, 16 postnatal and 12 conducted both before and after birth. Nearly all targeted infant and/or maternal nutrition. Studies varied widely in design, obesity risk factors, outcomes and quality. Overall, nine interventions of varying quality reported some evidence of significantly improved child weight trajectory, although effects tended to diminish over time. Interventions that improved weight outcomes tended to engage parents for a longer period, and most offered health professional input and support. Two studies of limited quality reported significantly worse weight outcomes in the intervention group.